Structural determinants of stunting among children aged 0–59 months: A PLS-SEM analysis of family, environmental, and health factors in Banten, Indonesia - Adam Sugiharto; Megawati Simanjuntak; Yulina Eva Riany; Muhammad Rizal Martua Damanik; Diah Krisnatuti (AcTion: Aceh Nutrition Journal, 2026)
Stunting remains a major public health problem among children under five years of age in Indonesia, particularly among socioeconomically vulnerable families. Previous studies have mostly examined stunting determinants separately and rarely analyzed their structural relationships. This study aimed to analyze the structural relationships between family economic pressure, access to health facilities, feeding practices, and child nutritional status using Partial Least Squares Structural Equation Modeling (PLS-SEM). A cross-sectional study was conducted from July to September 2025 in Sumur District, Banten Province, Indonesia, involving 402 mothers with children aged 0–59 months from families at risk of stunting. Data were collected through structured interviews, anthropometric measurements and standardized questionnaires. Data were analyzed using SPSS 23 and SmartPLS 3.0. PLS-SEM analysis showed that family economic pressure significantly influenced feeding practices (β = 0.321; p < 0.001), and access to health facilities positively affected feeding practices (β = 0.130; p = 0.024). However, feeding practices did not significantly influence HAZ (β = 0.015; p = 0.768). Birth weight was associated with the nutritional status of the child. In conclusion, these findings highlight the importance of strengthening economic resilience and improving access to supportive health services in family based stunting prevention strategies.